2014
DOI: 10.1177/0310057x1404200607
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Escalation of Care by Junior Medical Officers

Abstract: Patients can acutely deteriorate unexpectedly. Junior medical officers (JMOs) are often first to review patients who become unwell. Opportunities to escalate care to a senior colleague may exist prior to the need for a rapid response team review. Little is known about the factors that influence JMO decisions to escalate care. In this study, our objective was to investigate the self-reported factors that influence escalation of care by JMOs in a university-affiliated, tertiary level hospital. We designed a face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
(13 reference statements)
1
21
0
Order By: Relevance
“…Stewart et al showed that trainees, in an effort to avoid displaying knowledge gaps or slowing down the clinical team, will only ask for help when they are convinced not doing so would harm the patient [57]. Another study reported that 30% of residents found it difficult, when they were busy, to pursue input from supervisors [58]. Thirty-six percent did not escalate care because they did not want to wake up supervisors.…”
Section: Discussionmentioning
confidence: 99%
“…Stewart et al showed that trainees, in an effort to avoid displaying knowledge gaps or slowing down the clinical team, will only ask for help when they are convinced not doing so would harm the patient [57]. Another study reported that 30% of residents found it difficult, when they were busy, to pursue input from supervisors [58]. Thirty-six percent did not escalate care because they did not want to wake up supervisors.…”
Section: Discussionmentioning
confidence: 99%
“…Each study developed a new local survey tool to address specific study aims except one, which used a locally modified version of a previously developed tool (Beebe et al., ). Only four referenced other work to inform the development or administration of the instrument (McIntyre et al., ; Pusateri, Prior, & Kiely, ; Rotella, Yu, Ferguson, & Jones, ; Stevens et al., ). While all studies reported that the newly developed surveys had pretesting prior to distribution, none provided any convincing evidence of instrument reliability or validity.…”
Section: Quality Appraisal Of Study Methodsmentioning
confidence: 99%
“…Three studies provided clear justification for sample size calculations (Plowright et al., ; Sarani et al., ; Stevens et al., ), and four described representativeness of the sample (Jones et al., ; Pusateri et al., ; Sarani et al., ; Stevens et al., ), and the population sampling frame (Jones et al., ; Rotella et al., ; Sarani et al., ; Stevens et al., ). Ethics approval was noted in every study, with three exempted as local quality improvement surveys (Plowright et al., ; Salamonson et al., ; Stevens et al., ).…”
Section: Quality Appraisal Of Study Methodsmentioning
confidence: 99%
See 2 more Smart Citations